URBANIZATION AND SPATIAL CHANGES IN DEMOGRAPHIC CHARACTERISTICS IN MONTERREY METROPOLITAN REGION - Acharya, Arun Kumar (2011)
This paper tries to explore the process of urbanization and spatial changes in demographic features in the Monterrey Metropolitan Region (MMR), Mexico. This city is the third largest urban sector in Mexico which has around 4 million population. It is also the industrial and economic capital of the country. The present study found that rapid urbanization in the metropolitan region has a close association with process of industrialization. In population distribution and composition, study found that the metropolitan region had its "demographic transition" during the years seventies and currently the region is taking advantages of demographic bonus cohort, i.e. a higher concentration of population in economic active groups compare to children and old age population. However, this paper indentified a higher imbalance in metropolitan demographic scenario. On the one hand, there is di-populization in the city center region and in other there is a steady increment of population in peri-urban region.